Strategies for Islamic Education Teachers in Dealing with the Impact of the Zoning System on New Student Admissions - Rahmadiati, Rahmadiati; Sarwan, Sarwan; Batubara, Juliana (International Journal of Multidisciplinary Research of Higher Education, 2025)
The process of accepting new students using the zoning system has an impact on students' morals, religious practices, and learning processes. The purpose of this study is to provide an overview of the efforts of Islamic Education teachers in dealing with the impact of the zoning system for accepting new students. This study uses a descriptive qualitative method. The sources of data for this study were Islamic Education teachers, Guidance Counseling teachers, student representatives, and school principals, with data collection techniques through observation, interviews, and documentation. The data were analyzed, reduced, and presented in narrative form, after which conclusions were drawn. This study found that the efforts made by Islamic Education teachers in coping with the impact of the zoning system for new student admissions related to moral violations and enthusiasm in practicing worship were to reprimand students and encourage them to always do good deeds. In addition, Islamic Education teachers coordinated with each other, including homeroom teachers, guidance counselors, school administrators, and parents. To mitigate the impact of the zoning system for new student admissions on the diversity of students' abilities and learning styles, teachers taught according to standard processes, including efforts to implement differentiated learning as recommended by the government.